The Relationship between Mental Health and Work Productivity in Office Workers in the Era of Hybrid Working - Sri Ariyanti; Meiana Harfika; Ali Imran; Fransina Tubalawony; Wahidyanti Rahayu Hastutiningtyas (Benih : Journal of Midwifery, 2025)
The hybrid working era that combines work in the office and from home poses its own challenges related to workers' mental health that can potentially affect work productivity. This study aims to examine the relationship between mental health, as measured through the variables of job stress, psychological anxiety, and emotional balance, to work productivity in office workers in the hybrid working era. The method used was a quantitative survey with a sample of 200 office workers, analyzed using multiple linear regression. The results showed that work stress and psychological anxiety had a significant negative effect on work productivity, while emotional balance had a significant positive effect. The regression model used was able to explain 53.6% of the variation in work productivity. In addition, classical assumption testing confirmed that the research model was free from multicollinearity and heteroscedasticity, so the validity and reliability of the results can be accounted for. The findings confirm the importance of mental health management in supporting work productivity in a dynamic hybrid working environment. The practical implication of this study is the need for organizations to design intervention programs that reduce stress and anxiety while improving workers' emotional balance in order to achieve optimal performance. This research provides an empirical contribution to the development of mental health and work productivity literature in the era of work pattern transformation.